Analysis of The Application Withholding, Depositing, and Reporting Income Tax Article 23 on Services In Private Companies - Adevansyah Wika Mulia Nanda; Binti Azizatun Nafi'ah (Universitas Muhammadiyah Makassar, 2025)
This study analyzes the application of Income Tax Article 23 (PPh 23) withholding, depositing, and reporting in service transactions at PT Aryan Pembangunan Perumahan Properti (KidZania Surabaya), a company operating in education and entertainment services. The research aims to assess the compliance of the company with PPh 23 regulations, particularly focusing on service-related payments subject to a 2% withholding tax rate. Using a qualitative descriptive approach, primary data were collected through direct interviews and observations of the company’s tax management practices. Secondary data from relevant tax laws and literature were also reviewed to support the analysis. The findings reveal that while the company accurately calculates the withholding tax based on applicable rates, there are delays in the depositing and reporting processes. These non-compliances may be attributed to internal procedural inefficiencies or lack of adequate understanding of tax obligations. The study underscores the importance of timely tax depositing and reporting to avoid penalties and ensure adherence to Indonesian tax regulations. Recommendations include improving internal controls, staff training on tax compliance, and adopting systematic electronic reporting methods. This research contributes to understanding tax compliance challenges faced by private companies in Indonesia and offers practical insights for enhancing the application of Income Tax Article 23 in service transactions.